Knowledge, attitude, and practice of primary care physicians for pretravel counseling for type 2 diabetes patients in Jazan Region, Kingdom of Saudi Arabia - Ibrahim M. Alhumsi (Journal of Family Medicine and Primary Care, 2023)
Background and Objective: Pretravel advice given by the primary healthcare (PHC) physicians is of vital importance to diabetic patients to maintain their glycemic status during their travel as many of them are not aware of the risks of travel on their health status. Our objective was to assess the status of pretravel counseling for type 2 diabetic patients (knowledge, attitude, and practice) in Jazan Region, Kingdom of Saudi Arabia (KSA) among the PHC physicians. Materials and Methods: A cross-sectional study was carried out among a sample of PHC physicians working at the PHC centers in Jazan Region, KSA. The data were collected using a validated self-administered questionnaire. Results: The study included 250 PHC physicians. The age of 45.2% of them ranged between 30 and 39 years, and males represented 56.2% of them. Overall, the knowledge score ranged between 0 and 10 with a median (interquartile range [IQR]) of 6 (5–7). Physicians aged 40–49 years (P < 0.001), non-Saudis (P = 0.005), and more experienced physicians (>15 years) (P < 0.001) were more knowledgeable than their counterparts. The attitude score ranged between 6 and 30 with a median (IQR) of 25 (22–27). Saudi physicians were more likely than non-Saudis to have more positive attitude toward pretravel counseling for diabetic patients (P = 0.007). The practice score ranged between 1 and 13 with a median (IQR) of 6 (5–8). Conclusion: The PHC physicians in Jazan Region, KSA, had a moderate level of knowledge and practice as well as encouraging attitude concerning pretravel counseling for type 2 diabetic patients. However, their knowledge and attitude from one side were not associated with their practice from the other side.